Erythema nodosum-like lesion in sarcoidosis: a specific skin manifestation occasionally seen in Japanese patients - Ishikawa, Masato; Yamamoto, Toshiyuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Erythema nodosum-like sarcoid lesion is a specific form of cutaneous sarcoidosis sometimes observed in Japanese patients, with a female predominance, involving the lower extremities. By contrast, erythema nodosum as a non-specific cutaneous manifestation associated with sarcoidosis is rare in Japan. Erythema nodosum-like sarcoid lesion resembles erythema nodosum only in appearance, but histologically shows sarcoid granulomas.Objectives: To determine the clinical characteristics of erythema nodosum-like sarcoid lesion.Methods: We examined the clinical characteristics of erythema nodosum-like sarcoid lesion in our patients with sarcoidosis. Clinical charts were retrospectively examined from 2000 to 2019. The patients’ data, such as age, gender, types of cutaneous lesion, serum levels of angiotensin-converting enzyme, and extracutaneous organ involvement, were evaluated. We also reviewed cases of erythema nodosum-like sarcoid lesion reported in previous literature.Results: Among 101 cutaneous sarcoidosis patients, eight were diagnosed as having erythema nodosum-like sarcoid lesion in our department. The patients were one male and seven females, and their ages ranged from 30 to 74 years old. All cases involved the lower extremities. The serum angiotensin-converting enzyme level was elevated in five cases. Lung sarcoidosis was observed in all cases, and ocular sarcoidosis was observed in six cases, whereas no patients had cardiac sarcoidosis.Conclusions: Although erythema nodosum-like sarcoid lesion may not be major skin manifestation of sarcoidosis, erythema nodosum-like sarcoid lesion frequently accompanies lung and ocular sarcoidosis. Thus, we should pay much attention to erythema nodosum-like sarcoid lesion for early identification of patients needing workup for systemic illness.